Peer Relationships and Access to Pornographic Media on Adolescent Sexual Behavior - Andrianto, Muhammad Bagus; Devi, Yufita; Padila, Padila; Arifin, Nur Afni Wulandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between peers and access to pornographic media on adolescent sexual behavior at the Faculty of Health Sciences, Muhammadiyah University of Bengkulu. The research method used is analytical survey research with a cross-sectional approach. The results of the study show that univariate analysis calculations can explain that the actions of respondents' peers have little influence on the sexual behavior of adolescent respondents (52.1%), the majority (37.5%) of respondents rarely access pornographic media, and as many as 82.3% of respondents never carry out this behavior. In conclusion, there is no relationship between peers and access to pornographic media on adolescent sexual behavior. Keywords: Pornographic Media, Sexual Behavior, Teenagers, Peers